Effect of thickness and inclination angle of weakly cemented interlayer on fracture development and fracture energy evolution of rock mass - Chengen Qi; Bo Wang; Yifei Mao; Zhu Li; Tingye Qi; Guozhong Hu; Wei Qin; Jing Zhu (Scientific Reports)
Abstract In response to the common issue of instability and failure of weak interlayers under load in geotechnical engineering, a discrete element simulation study plan consisting of 25 schemes was designed, with the inclination and thickness of the interlayer as variables. Based on the test results from a universal testing machine, the weak interlayer and adjacent rock mass simulation parameters were calibrated. A Fish program was developed to monitor the evolution of cracks, the number of tension and shear cracks, block elastic strain energy, and tension and shear strain energy throughout the uniaxial compression process. This study reveals the influence of the inclination and thickness of the interlayer on the evolution of the "main rupture crack morphology—changes in the number of tension and shear cracks—energy accumulation and dissipation" under uniaxial compression conditions, as well as the interrelationship among these three factors. The results show that (1) when the interlayer thickness is the same, as interlayer inclination increases from 0° to 60°, the strength of the specimen decreases by 38%-40%. Elastic strain energy is positively correlated with the peak strength of the specimen. When interlayer inclination angles are 0°, 15°, 30°, and 45°, the number of shear cracks and shear strain energy stored in the contact do not change significantly. However, when the interlayer inclination is 60°, compared to the specimen with the interlayer inclination of 45°, the number of shear cracks in the specimen decreases by 24.01% to 48.28%, and shear strain energy decreases by 35.06% to 50.35%. (2) When the interlayer inclination is the same, as the interlayer thickness increases from 4 to 12mm, the strength of the specimen decreases by 6.49% to 22.02%. The specimen’s total tension cracks increase by 38.1% to 143.52%, while tension strain energy decreases by 13.04% to 40%. The number of shear cracks and shear strain energy fluctuates, with increases being positive and decreases being negative, with ranges of -7.65% to 26.02% and -11.33% to 24.55%, respectively. (3) Under the influence of different interlayer thicknesses and inclinations, the number of shear fractures and their energies are significantly higher than those of tension fractures, and shear failure is the main reason for the failure and instability of weakly cemented interlayered rock mass. The research results can provide a reference for predicting and evaluating rock and soil mass failure modes and designing reinforcement schemes for projects with weak interlayers.